2017
DOI: 10.17305/bjbms.2017.1765
|View full text |Cite
|
Sign up to set email alerts
|

Knee stiffness and viscosity: New implementation and perspectives in prosthesis development

Abstract: The pendulum test is a method applied to measure passive resistance of the knee. A new and simple pendulum test with instrumentation based on infrared camera was used to evaluate knee stiffness and viscosity on a female human cadaver. The stiffness and viscosity were calculated based on the kinetic data. During the measurements, the periarticular and intraarticular soft tissue of the knee was gradually removed to determine the stiffness and viscosity as a function of the tissue removal rate. The measurements s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…This limits more detailed considerations of the extent to which the meniscus state affects the boundary friction coefficient (µ lin ) or the viscous friction (µ) and the viscous damping coefficient (c). Another limitation is that a passive pendulum friction device cannot simulate active muscle forces or provide stabilization of the patella, which has an influence on the joint kinematics (Bull and Amis, 1998;Bohinc et al, 2017). When evaluating joint friction based on kinematic data, this limits the comparability to the in vivo knee joint friction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This limits more detailed considerations of the extent to which the meniscus state affects the boundary friction coefficient (µ lin ) or the viscous friction (µ) and the viscous damping coefficient (c). Another limitation is that a passive pendulum friction device cannot simulate active muscle forces or provide stabilization of the patella, which has an influence on the joint kinematics (Bull and Amis, 1998;Bohinc et al, 2017). When evaluating joint friction based on kinematic data, this limits the comparability to the in vivo knee joint friction.…”
Section: Discussionmentioning
confidence: 99%
“…It was already stated that intraarticular ligaments and soft tissues have a significant effect on the viscous damping of a passive joint motion. For example, Bohinc et al found in their study that the viscous damping of a human leg oscillation decreased the more tissue was resected (Bohinc et al, 2017). Therefore, joint friction does not only depend on the boundary friction between the tibia, femur and the meniscus surfaces, but also on the viscous damping of the surrounding soft tissues (Charnley, 1960;Akelman et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…11 Passive pendulum test is one of the methods for calculating knee passive properties utilized for estimating the stiffness and viscosity parameters during the leg oscillation. 12,13 The limitation of the supplies and laboratory equipment for video recording systems, and the electro-goniometer errors due to possible movements with leg twists are the disadvantages of these methods Although most studies have used a nonlinear elastic element, all of them offer a wide range of models for the loss element of passive torque. 14,15…”
Section: Introductionmentioning
confidence: 99%